Evidence-based long term interventions targeting acute mental health presentations for children and adolescents: systematic review - Gerstl, Brigitte; Ahinkorah, Bright Opoku; Nguyen, Thomas P.; John, James Rufus; Hawker, Patrick; Winata, Teresa; Brice, Febe; Bowden, Michael; Eapen, Valsamma (Frontiers in Psychiatry, 2024)
Background Long term intervention services have proven to be effective in improving mental health (MH) outcomes and the quality of life for children and young people (CYP). Aim To synthesize evidence on the effectiveness of long-term interventions in improving MH outcomes for CYP, 0-17 years, presenting with MH conditions. Methods A systematic search was carried out and the methodological quality of included long term MH intervention studies were assessed. Six databases were searched for peer-reviewed articles between January 2000 and September 2022. Results We found 30 studies that reported on the effectiveness of a range of long-term MH interventions in the form of (i) group therapy, (ii) multisystemic behavior therapy, (iii) general services, (iv) integrated services, (v) psychotherapy, (vi) intensive intervention services, (vii) comprehensive collaborative care, (viii) parent training, and (ix) home outreach service. Among the included studies, seven were rated as high level of evidence based on the National Health and Medical Research Council (NHMRC) levels of evidence hierarchy scale and seven were of moderate quality evidence. Others were rated as lower-quality evidence. Among the studies providing high quality evidence, most were reported for group therapy, general services, and psychotherapy studies demonstrating beneficial effects. Conclusion This systematic review provides evidence to demonstrate the benefits of a range of long-term interventions, in a range of settings, can be effective in improving MH outcomes for CYP and their families. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022323324.